Air Historical Branch: Records (Series I) - Great Britain. Ministry of Air.; Australian Joint Copying Project; National Library of Australia; Library of New South Wales; Great Britain. Public Record Office (Canberra : Australian Joint Copying Project, 1911)
Records of the Air Historical Branch which was set up after World War I to collect, arrange and index records of the Royal Flying Corps, the Royal Air Force and the Air Ministry.
National Library of Australia holds microfilm master.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the Library of New South Wales.
Public Record Office Air 1, pieces 14-2424 (filmed selectively)
Also available online
Original held by Public Record Office, London.
Keywords: Great Britain. -- Ministry of Air -- Records and correspondence; Great Britain. -- Royal Air Force; Australia. -- Royal Australian Air Force; Air pilots -- Training of -- Commonwealth countries; Airships -- Commonwealth countries